Analisa Pengendalian Kualitas Produk Knob S/A Shift Lever pada PT. Injeksi Plastik Pasifik dengan Metode Six Sigma - Khanza, Savira Syahrani Al; Hasibuan , Bernard (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Pacific Plastic Injection is a rubber and plastics sector manufacturing company that produces automotive industry components. There are defects in the products produced by PT. Pacific Plastic Injection, namely in Knob S/A Shift Lever products. The purpose of this study is to identify the cause of the defect, obtain sigma level values for Knob S/A Shift Lever products, and provide improvement proposals. The results of this study found types of defects, namely short shot, sink mark, cracking, bubble, weldline, and silver. The factors causing disability come from humans (man) and machines (machine). The DPMO value at the measure stage is 4165.86 which if converted into a sigma level is 4.3. The DPMO value at the measure stage is 4165.86 which if converted into a sigma level is 4.3 This shows that the quality control process at PT. Pacific Plastic Injection is quite good, because it is still within the average Sigma level of USA companies which is at the level of-4 sigma. The improvement proposals provided are providing direction and training for workers regarding the production process, adjusting machines according to procedures, giving directions to workers to follow SOPs, improving production process SOPs, ensuring products have hardened before being released from molding, and checking raw materials before entering the machine.